Mình ko thêm bớt hạng tử nhé.
\(8x^3-3x+6x^2-1\)
\(=\left(8x^3-1\right)+\left(6x^2-3x\right)\)
\(=\left(2x-1\right)\left(4x^2+2x+1\right)+3x\left(2x-1\right)\)
\(=\left(2x-1\right)\left[\left(4x^2+2x+1\right)+3x\right]\)
\(=\left(2x-1\right)\left(4x^2+5x+1\right)\)
\(=\left(2x-1\right)\left[4x\left(x+1\right)+\left(x+1\right)\right]\)
\(=\left(2x-1\right)\left(x+1\right)\left(4x+1\right)\)
\(8x^3-3x+6x^2-1=\left(8x^3-12x^2+6x-1\right)+\left(18x^2-9x\right)\)
\(=\left(\left(2x\right)^3-3\cdot\left(2x\right)^2\cdot1+3\cdot2x\cdot1^2-1^3\right)+\left(18x^2-9x\right)\)
\(=\left(2x-1\right)^3+9x\left(2x-1\right)=\left(2x-1\right)\left(\left(2x-1\right)^2+9x\right)\)
\(=\left(2x-1\right)\left(4x^2-4x+1+9x\right)=\left(2x-1\right)\left(4x^2+5x+1\right)\)
bạn giải thích bước thêm bớt hạng tử dc k